Data Structures, Files and Databases - Bamford, Carl; Curran, Paul (Computer Science Series, 1991)
The text is an introduction to data structures, files and databases appropriate for use as a second year BSc Computing text, or for the final year of a HND Computer Studies course. It provides the reader with an introduction to the techniques and underlying theory used in the design of structured data. Revised and extended, with additional chapters on SQL and 4GL's